An experimental investigation on the effects of air on filmwise condensation of PF-5060 dielectric fluid on plain and finned tube bundles - Liu, P. (2021)
In this paper, filmwise condensation of PF-5060 on plain and finned tubes in the presence and the absence of air was experimentally studied in a condensation chamber. The enhanced tubes were of integral and jagged fin structures. Based on our experimental results, it is found that a slight amount of air in the system can lead to a large decrease in the heat transfer coefficient. The influence of air is more significant for condensation on finned tubes due to the flooding effect of the diffusion layer. When only 0.51 wt% of air is introduced into the system, the condensation heat transfer coefficient decreases by about 26% on plain tubes while it decreases by a substantial 50% on finned tubes as compared to the pure vapor condition. However, a further increase in the air concentration has a less significant effect on the heat transfer coefficient, especially for condensation on finned tubes. In order for the finned tubes to have significant advantage in condensation heat transfer performance over plain tubes, the system has to operate below 0.51 wt% of air. If the system is required to operate above 0.51 wt% of air, the use of plain tubes is sufficient as the finned and plain tubes show similar condensation heat transfer performance. This is mainly due to the dominant diffusion layer flooding effect on the finned tubes. Visualization of different condensation phenomena have been conducted from which the condensation modes were found to be mainly dripping mode and column mode. Existing condensation correlations were analyzed and compared against the present experimental results, from which the possible transport mechanisms in the condensation of PF-5060 were identified. On this basis, a new correlation was developed which is able to predict all the present results with an accuracy of ±25%.